Recent Progress on C-4-Modified Podophyllotoxin Analogs as Potent Antitumor Agents - Liu, Ying-Qian; Tian, Jing; Qian, Keduo; Zhao, Xiao-Bo; Morris-Natschke, Susan L.; Yang, Liu; Nan, Xiang; Tian, Xuan; Lee, Kuo-Hsiung (Medicinal research reviews, 2015)
Podophyllotoxin (PPT), as well as its congeners and derivatives, exhibits pronounced biological activities, especially antineoplastic effects. Its strong inhibitory effect on tumor cell growth led to the development of three of the most highly prescribed anticancer drugs in the world, etoposide, teniposide, and the water‐soluble prodrug etoposide phosphate. Their clinical success as well as intriguing mechanism of action stimulated great interest in further modification of PPT for better antitumor activity. The C‐4 position has been a major target for structural derivatization aimed at either producing more potent compounds or overcoming drug resistance. Accordingly, numerous PPT derivatives have been prepared via hemisynthesis and important structure–activity relationship (SAR) correlations have been identified. Several resulting compounds, including GL‐331, TOP‐53, and NK611, reached clinical trials. Some excellent reviews on the distribution, sources, applications, synthesis, and SAR of PPT have been published. This review focuses on a second generation of new etoposide‐related drugs and provides detailed coverage of the current status and recent development of C‐4‐modified PPT analogs as anticancer clinical trial candidates.